O strategicznym zarządzaniu kosztami - Nowak, Edward; Nowak, Marta (On Strategic Cost Management, 2005)
The article is devoted to the problem of strategy-orientated cost management. Against the background of cost leadership strategy of a company, the essence of strategic cost management has been presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 284-288